Dynamic calibration system for seismometers: Traceability from 0.03 Hz up to 30 Hz. (December 2021) - Schiavi, Alessandro; Prato, Andrea; Pejrani, Giulia; Facello, Alessio; Mazzoleni, Fabrizio
Abstract: Mechanical calibration and traceability of seismometers in operating conditions are still a technical challenge, since very low-frequency ranges (below 0.1 Hz) are involved, and sensors under investigation are generally heavy and bulky. Recently, within the vibration metrology field, some pioneering works proposed to evaluate the seismometers' sensitivity by applying laboratory mechanical calibration procedures, against primary or secondary standards, according to the ISO 16063 methods. By following this path, at INRIM, it has been developed a suitable system for short period horizontal and vertical ground velocity calibration of 3-axis seismometers. The calibration system allows to directly evaluate the sensitivities of the 2 axes perpendicular to the gravity field, with respect to the horizontal ground velocity (S-waves), and to derive the sensitivity of the vertical axis, parallel to the gravity field, with respect to the vertical ground velocity (P-waves), in the frequency range between 0.03 Hz and 30 Hz.